Cu-doped SnO2 nanoparticles: size and antibacterial activity investigations - Aragón, F. F.H.; Villegas-Lelovsky, L. [UNESP]; Castillo-Llanos, J. I.; Soncco, C. M.; Solis, J. L.; Peralta-Alarcón, G. H.; Pacheco-Salazar, D. G.; Morais, P. C. (Royal Society of Chemistry (RSC), 2023)
Nowadays, the use of self-cleaning surfaces is increasing globally, especially after the COVID-2019 pandemic, and the use of nanoparticles has been shown as a plausible option for this purpose. In the present study, Cu-doped SnO2 nanocrystals were successfully synthesized (in the copper content range of 0-30 mol%) using the polymeric precursor method. The structural, morphological, vibrational, and antibacterial activity were carefully studied to unveil the effect of copper ions on the properties of the hosting matrix, aiming at maximizing the usage of Cu-doped SnO2 nanocrystals. The results show fabrication of nanoparticles near their respective exciton Bohr diameter (5.4 nm for SnO2), however, monophasic SnO2 was observed up to 15 mol%. Above this limit, a secondary CuO phase was observed, as shown by the assessed X-ray diffraction (XRD), Fourier transform infrared, and Raman spectroscopy data. Furthermore, the redshift of the primary A1g vibrational mode of SnO2 is successfully described using the phonon-confinement model, demonstrating a good relationship between the Raman correlation length (L) and the crystallite size (〈D〉), the latter determined from XRD. Regarding the antibacterial activity, assessed via the disc-diffusion testing method (DDTM) while challenging two bacterial species (S. aureus and E. coli), our results suggest a rapid diffusion of the nanoparticles out of the paper disc, with a synergistic effect credited to the Sn1−xCuxO2-CuO phases contributing to the inhibition of the bacteria growth. Moreover, the DDTM data scales with cell viability, the latter analyzed using the Hill equation, from which both lethal dose 50 (LD50) and benchmark dose (BMD) were extracted.